Procedure for deformation detection using STARNET - Setan, Halim; Ibrahim, M. S. (2003)
The main steps in the deformation detection via geodetic methods are the least square estimation (LSE) of each epoch, and the deformation detection between epochs. This research focuses on the development of an interface programs called CONVERT, to integrate STARNET V6 (a commercial software) and our in-house software (DEFORM99 and GPSAD 2000), for deformation detection between two epoch (for 2D and 3D applications respectively). In this research, STARNET V6 is used first for LSE of each epoch due to its powerful adjustment capabilities. Next, CONVERT reads the special files created by STARNET, and create the appropriate input files for DEFORM99 and GPSAD 2000. An example is included to show the possibility of using output from STARNET for deformations detection applications.